Rural and Urban High School Dropout Rates: Are They Different? - Jeffrey L. Jordan; Genti Kostandini; Elton Mykerezi (Journal of Research in Rural Education, 2012)
This study estimates the high school dropout rate in rural and urban areas, the determinants of dropping out, and whether the differences in graduation rates have changed over time. We use geocoded data from two nationally representative panel household surveys (NLSY 97 and NLSY 79) and a novel methodology that corrects for biases in graduation rates (Heckman and La Fontaine, 2010). Our findings suggest that high school graduation rates are very similar across the rural-urban continuum in the early 2000s, and they are lower by 3 percentage points compared to the 1980s, with the decline experienced uniformly across the rural-urban continuum. We find that gender, family assets, the presence of biological parents, and maternal attributes appear to be the main determinants of graduation and influence graduation in a similar way across both urban and rural areas. For years, the research literature has looked at various issues from a perspective of determining how rural and urban areas are different with regard to high school dropout rates. We suggest that once family attributes are accounted for differences in rural and urban areas are small and narrowing.